1978
DOI: 10.1073/pnas.75.12.5964
|View full text |Cite
|
Sign up to set email alerts
|

Origin of DNA replication in papovavirus chromatin is recognized by endogenous endonuclease.

Abstract: Isolated simian virus 40 (SV40) and polyoma nucleoprotein complexes contain endonuclease that, under in vitro conditions, converts part (up to 30%) of the covalently closed superhelical DNA to full-length linear rods. The positions of the cleavage sites within the genomes of SV40 and polyoma were determined by digestion with various single-cut restriction endonucleases and subsequent agarose gel electrophoresis of the cleavage products. Both SV40 and polyoma covalently closed superhelical DNA were cleaved open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
46
1
1

Year Published

1981
1981
1987
1987

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(52 citation statements)
references
References 29 publications
4
46
1
1
Order By: Relevance
“…Major barriers to Bal3l digestion appear to define the outer borders of the region of SV40 chromatin previously shown to be preferentially cleaved by endonucleases (7,8,(31)(32)(33)(38)(39)(40). These borders appear as clusters of Bal3l stop sites located between nucleotides 390 and 450 on the late side (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major barriers to Bal3l digestion appear to define the outer borders of the region of SV40 chromatin previously shown to be preferentially cleaved by endonucleases (7,8,(31)(32)(33)(38)(39)(40). These borders appear as clusters of Bal3l stop sites located between nucleotides 390 and 450 on the late side (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A short segment of the viral genome (ca. 400 base pairs [bp] extending from the SV40 origin of replication in the late direction) is hypersensitive to endonuclease cleavage (33,(38)(39)(40) and appears, in the electron microscope, as a region which is free of nucleosomes (19,32). Recently, more detailed studies have shown that, within the nuclease-sensitive site, there are subregions with differential sensitivity to DNase 1 (7,8,31,32).…”
mentioning
confidence: 99%
“…The availability of an amplified, homogeneous DNA species in a chromatin-like structure has provided convenient material for the study of specific features of chromatin. Of particular interest is the short region adjacent to the viral origin of replication (ori site) which is hypersensitive to cleavage by endonucleases (23,26,27,29) and which appears as a gap in the nucleosome pattern when visualized in the electron microscope (16,22). This region contains the early and late gene promoters, the transcriptional enhancer sequences, and the viral origin of replication.…”
mentioning
confidence: 99%
“…Data reported in the literature suggest the occurrence of nucleosome phasing at the SV40 regulatory region (15,16,23,24), although the molecular basis of this process is obscure. Our results provide the first experimental evidence suggesting that there is a preferred phasing of the histone octamers within the ori region of SV40.…”
Section: Discussionmentioning
confidence: 99%